Ressentiment: A Complex Emotion or an Emotional Mechanism of Psychic Defences? - Salmela, Mikko (2021)
Ressentiment is central for understanding the psychological foundations of reactionary politics, right-wing populism, Islamic fundamentalism, and radicalism. In this article we theorise ressentiment as an emotional mechanism which, reinforcing a morally superior sense of victimhood, expedites two parallel transvaluation processes: What was once desired or valued, yet unattainable, is reassessed as something undesirable and rotten, and one’s own self from being inferior, a loser, is reassessed as being noble and superior. We establish negative emotions of envy, shame, and inefficacious anger as the main triggers of ressentiment, with their associated feelings of inferiority and impotence, which target the vulnerable self. We identify the outcomes of ressentiment as other-directed negative emotions of resentment, indignation, and hatred, reinforced and validated by social sharing. We map the psychological structure of ressentiment in four stages, each employing idiosyncratic defences that depend on the ego-strength of the individual to deliver the transvaluation of the self and its values, and finally detail how social sharing consolidates the outcome emotions, values, and identities in ressentiment through shallow twinship bonds with like-minded peers. Our interdisciplinary theoretical account integrates classic philosophical scholarship of ressentiment and its contemporary proponents in philosophy and sociology, which highlight envy as the prime driver of ressentiment; it also considers the sociological approaches that focus on the repression and transmutation of shame and its social consequences, as well as the psychoanalytic scholarship on psychic defences and political psychology models on the emotionality of decision-making. We conclude the article by elaborating the political implications of ressentiment as the emotional mechanism of grievance politics.